New Last Glacial Maximum ice thickness constraints for the Weddell Sea Embayment, Antarctica - Nichols, Keir A.; Goehring, Brent M.; Balco, Greg; Johnson, Joanne S.; Hein, Andrew S.; Todd, Claire (The Cryosphere, 2019)
We describe new Last Glacial Maximum (LGM) ice thickness constraints for three locations spanning the Weddell Sea Embayment (WSE) of Antarctica. Samples collected from the Shackleton Range, Pensacola Mountains, and the Lassiter Coast constrain the LGM thickness of the Slessor Glacier, Foundation Ice Stream, and grounded ice proximal to the modern Ronne Ice Shelf edge on the Antarctic Peninsula, respectively. Previous attempts to reconstruct LGM-to-present ice thickness changes around the WSE used measurements of long-lived cosmogenic nuclides, primarily Be-10. An absence of post-LGM apparent exposure ages at many sites led to LGM thickness reconstructions that were spatially highly variable and inconsistent with flow line modelling. Estimates for the contribution of the ice sheet occupying the WSE at the LGM to global sea level since deglaciation vary by an order of magnitude, from 1.4 to 14.1m of sea level equivalent. Here we use a short-lived cosmogenic nuclide, in situ-produced C-14, which is less susceptible to inheritance problems than Be-10 and other long-lived nuclides. We use in situ C-14 to evaluate the possibility that sites with no post-LGM exposure ages are biased by cosmogenic nuclide inheritance due to surface preservation by cold-based ice and non-deposition of LGM-aged drift. Our measurements show that the Slessor Glacier was between 310 and up to 655m thicker than present at the LGM. The Foundation Ice Stream was at least 800m thicker, and ice on the Lassiter Coast was at least 385m thicker than present at the LGM. With evidence for LGM thickening at all of our study sites, our in situ C-14 measurements indicate that the long-lived nuclide measurements of previous studies were influenced by cosmogenic nuclide inheritance. Our inferred LGM configuration, which is primarily based on minimum ice thickness constraints and thus does not constrain an upper limit, indicates a relatively modest contribution to sea level rise since the LGM of < 4.6 m, and possibly as little as < 1.5 m.